Globalisation and the euro area: simulation based analysis using the New Area Wide Model - Roland Straub; Pascal Jacquinot (European Central Bank (ECB), 2008)
In this paper, we utilise the multi-country version of the NAWM to analyse the impact of globalisation on euro area macroeconomic aggregates. We provide alternative model-based definitions of globalisation associated with an increase in potential output in emerging Asia and its impact on total factor productivity in the euro area, and a shift in international specialisation patterns leading to changes in relative demand and import substitutions. The results indicate that globalisation has a positive impact on output, consumption, investment and real labour income in the long-run. This impact is driven by the improvement in the terms of trade and associated positive wealth effects, as well as by spillovers of higher potential output in emerging Asia on euro area total factor productivity. Additionally, we provide evidence that structural reforms in goods and labour markets would amplify the benefits associated with globalisation.
Keywords: E32; E62; 330; DSGE modelling; euro area; Globalisation; Wirtschaftswachstum; Bruttoinlandsprodukt; Reallohn; Privater Konsum; Handelseffekt; Globalisierung; Eurozone; Dynamisches Gleichgewicht; EU-Staaten